DEMOCRACY IN TIMES OF UBIQUITOUS SURVEILLANCE - Monteagudo, Ricardo [UNESP] (Univ Estado Rio Janeiro, 2021)
We intend to analyze the impact of Shoshana Zuboffs ideas on democracy in In the Age of Surveillance Capitalism. Digital corporations have pragmatic and financial interests with the extraction of information freely donated by users of digital media and social media. Public and governmental institutions intend to use the data to search for potential criminals and terrorists, however they must comply with their countries legislation. Corporations, on the other hand, are globalized companies that tend to consider and, eventually, establish new legislative criteria in the places where they operate, especially because the services they offer are new, and from recent technological innovations. Sovereignty and the modern idea of people have lost political substance in the face of corporations' superpower. Every citizen now represents a control device in surveillance capitalism while celebrating the benefits of technology. Big data and artificial intelligence dramatically reduce democratic liberties in a space where the promise of freedom has encouraged futuristic and libertarian hopes. With that, there is a new conceptual panorama to rethink the conditions of democracy.
Keywords: social contract; behavioral surplus; ideology; governmentality